What's Tropical About Nick Joaquin's Tropical Gothic?: Heat and Corporeality in "The Summer Solstice" and "The Dying Wanton" - Ang, Ann (Archīum Ateneo, 2024)
Since their first publication in magazines like Philippines Graphic and the Philippine Free Press, and their subsequent re-publication under the collection title Tropical Gothic, Nick Joaquin’s classic short stories from the 1940s have been mainly appraised within a gothic framework. While critics have read the doublings and monstrous excesses of these stories as expressing a postcolonial resistance to colonial modernity, or a desirous anxiety for a pre-colonial Philippines, this paper discusses tropicality as a further localization of such gothic elements. By adopting a new materialist approach to ecological imaginaries, this article argues that the discourse of the tropical in Joaquin’s aesthetics exercises an agentic role in re-locating temperate climactic markers within the Philippines. After briefly tracing the broader intellectual history of the tropical and the gothic, the discussion turns to the tropical gothic as a distinct category for the refiguration of gothic tropes within a material and tropical aesthetics. By drawing on feminist materialisms, this article makes a case for understanding tropical heat in “The Summer Solstice” and “The Dying Wanton,” as a source of animation and motility. Further attention to transcorporeality in these stories reveals the transformative power of the tropical on human bodies in their more-than-human aspects. By departing from sociohistorical frameworks, this paper invites further consideration of Joaquin’s contributions to a Philippine materialist and environmental poetics.